Kajian Strukturalisme Levi-Strauss dalam Tradisi Bulusan sebagai Cerita Rakyat di Kudus, Jawa Tengah - Diki Wahyudi; Sahid Teguh Widodo; Firman Aziz; Wilma Silvia Y (Javanologi: International Journal of Javanese Studies, 2023)
This research is motivated by the existence of the annual tradition of Bulusan celebration as folklore in Kudus which is considered to have a structure. This study aims to describe the structures behind the Bulusan folklore in the Kudus community, Central Java. The formulation of the research problem is as follows: 1) Does the Bulusan folklore have a structure? 2) How is the transformation of the structure of the Bulusan folklore? This study uses a literature review method regarding various existing sources. The results of this study are as follows. 1) Bulusan story has a structure consisting of external structure, internal structure, and oppositional relations. 2) the transformation of the story is divided into six points, one of which is the Bulus transformation as a form of fertility and prosperity. Thus, this folklore about Bulus is relevant to be reviewed based on Levi Strauss structuralism analysis.